PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN KOMPUTER DALAM MENDUKUNG PERKULIAHAN METROLOGI - Wagiran Wagiran (Jurnal Kependidikan, 2008)
This study aimed at planning, constructing, and examining a computer-based learning media to support the implementation ofconstructivist learning in the metrology subject matter. The study usedthe Research and Development (RD) approach. The research stagesincluded: (1) competencies identification, (2) literature review, (3) software development, (4) quality testing, (5) empirical testing, (6) monitoring, (7) software revision, and (8) recording the program.Quantitative data were collected by means of observation sheets,depth interview, and documentation. Data were analyzed using thedescriptive quantitative analysis technique. The results showed that:(1 the quality of the developed media was 73, 13 % (good), (2) thequality of program presentation was at 72, 66 % (good), and (3) theresult of student testing was 76, 14 % (good). It was concluded thatthe developed media was appropriate for use in teaching and learningactivities.